Just trying to have school : the struggle for desegregation in Mississippi - Adams, Natalie G.; Adams, James Harold, 1955- (University Press of Mississippi, 2018)
"After the 1954 Brown v. Board of Education ruling, no state fought longer or harder to preserve segregated schools than Mississippi. This massive resistance came to a crashing halt in October 1969 when the Supreme Court ruled in Alexander v. Holmes Board of Education that "the obligation of every school district is to terminate dual school systems at once and to operate now and hereafter only unitary schools." Thirty of the thirty-three Mississippi districts named in the case were ordered to open as desegregated schools after Christmas break. With little guidance from state officials and no formal training or experience in effective school desegregation processes, ordinary people were thrown into extraordinary circumstances. However, their stories have been largely ignored in desegregation literature. Based on meticulous archival research and oral history interviews with over one hundred parents, teachers, students, principals, superintendents, community leaders, and school board members, Natalie G. Adams and James H. Adams explore the arduous and complex task of implementing school desegregation. How were bus routes determined? Who lost their position as principal? Who was assigned to what classes? Without losing sight of the important macro forces in precipitating social change, the authors shift attention to how the daily work of "just trying to have school" helped shape the contours of school desegregation in communities still living with the decisions made fifty years ago."--Provided by publisher